TINGKAT KINERJA PENYULUH PERTANIAN TANAMAN PANGAN DI BP3K KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Santi Santi; Dewangga Nikmatullah; Rio Tedi Prayitno (Lampung University, 2016)
This research aimed to analyze the performance level of food crops agriculturalextension workerand the factors that related to the performance level of food crops agricultural extension worker. This research was conducted in Gadingrejo Subdistrict Pringsewu District. Respondents of this research were 109 peoples that consist of 10 food crops agriculturalextension worker which is choosen by purposive sampling, and 99 farmers under construction of food crops agriculturalextensionworker which is choosen bysimple random sampling. The performance level of agricultural extension worker in this research will be analyzed descriptively. Hypothesis was analyzed by rank spearman correlation. The result of this research showed that the performance level of agricultural extension worker in BP3K Gadingrejo Subdistrict included in low classification. The internal factors like the motivation level, the income level, and the education level did not have real relationto the performance level of agriculturalextension worker in BP3K Gadingrejo Subdistrict. The external factors like the farmers numbers under construction and the distance between their houses did not have significant relation, while other external factor was a reward system that have significant relation to the performance level of agricultural extension worker in BP3K Gadingrejo Subdistrict.Key words: agricultural extention, internal-eksternal factors, performance